Safety climate and driving behaviour: Differential effects on truck drivers’ violations and errors - Laura Meyer; Leila Louise Goedhals-Gerber; Anneke de Bod (Transportation Research Interdisciplinary Perspectives)
Safety climate – the shared perceptions of safety’s importance within an organisation – is a strong predictor of aberrant driving behaviours. This study employs Partial Least Squares Structural Equation Modelling (PLS-SEM) on a sample of 110 tanker drivers at a major South African trucking company to model the relationship between safety climate and two classes of aberrant driving behaviours – errors and violations. A multilevel model measuring safety climate using organisation-level safety climate (OSC) and group-level safety climate (GSC) is followed, with OSC fully mediated by GSC in its effect on driver behaviour. The findings show safety climate has a significantly larger impact on driving violations than errors, as safety climate affects the driving behaviour largely through safety motivation, which has a greater impact on categorically intentional violation behaviours, as opposed to habitual, unintentional errors. The study also demonstrates that safety climate explains a larger portion of the variation in violations than errors, suggesting that violations may be more sensitive to changes in safety climate, supervisory behavioural integrity, and safety motivation. Interventions leveraging safety climate may thus be more effective at reducing violations than errors. Future research should investigate the precursors to driving errors, as addressing these may require remedial training rather than changes in safety climate to achieve substantial improvements.